1971
DOI: 10.1302/0301-620x.53b3.425
|View full text |Cite
|
Sign up to set email alerts
|

Intercondylar T-Shaped Fractures of the Humerus

Abstract: 1. A review of ten cases of T-shaped intercondylar fractures of the humerus treated with a sling and early movement is presented. 2. The method and the results are discussed and some comparison is made with other series. 3. This method of treatment has certain advantages and the results are reasonable in comparison with those of other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(14 citation statements)
references
References 4 publications
0
10
0
2
Order By: Relevance
“…The cuff is removed after six weeks and the elbow is then mobilised. Good results have been reported using this method in a "bag of bones" osteoporotic setting [1]. In contrast, other authors reported worse results on nonoperated patients versus operated patients in terms of pain, function and range of motion [13].…”
Section: Discussionmentioning
confidence: 99%
“…The cuff is removed after six weeks and the elbow is then mobilised. Good results have been reported using this method in a "bag of bones" osteoporotic setting [1]. In contrast, other authors reported worse results on nonoperated patients versus operated patients in terms of pain, function and range of motion [13].…”
Section: Discussionmentioning
confidence: 99%
“…Disadvantages are non-union and hardware prominence related to osteotomy and linked visualization of anterior articular surfaces. 3 In present study we used 3.5 mm reconstruction plates of appropriate size mostly which will be contoured according to the need and appropriate size cortical screws along with Kirschner wires and stainless steel wires for tension band wiring of osteotomised olecranon. Patient was placed in a lateral decubitus.…”
Section: Methodsmentioning
confidence: 99%
“…성인에 있어 비교적 드문 상완골 원위부의 골절은 대부분 이 주관절면을 침범하는 분쇄 골절로 치료가 어렵고 예후가 좋지 않은 것으로 알려져 왔다 4,11,14,22,26) . 치료 방법으로는 보 존적 치료와 수술적 치료가 있지만 최근에는 보존적 방법보 다는 관혈적 치료를 시행하는 것이 만족할 만한 결과를 얻 기 위한 최상의 방법이며 술 후 주관절 기능에 있어서 중요 하다고 보고되고 있다 6,12,13,30,31) .…”
Section: 서 론unclassified
“…Morrey의 평가법에 의한 임상적 결과의 판정은 40예 중 우수 15예 (37.5%), 양호 23예 (57.5%), 보통 2예 (5%)이었다 (Table 1) 4,10,19) . 발생 빈도는 Acker- …”
Section: )unclassified